Coronary computed tomography angiography and echocardiography in children with homozygous familial hypercholesterolemia. (June 2019) - Luirink, Ilse K.; Kuipers, Irene M.; Hutten, Barbara A.; Planken, Robrecht N.; Backx, Adrianus P.C.M.; Groothoff, Jaap W.; Wiegman, Albert
Abstract: Background and aims: Homozygous familial hypercholesterolemia (hoFH) is a rare genetic disease, hallmarked by a lifelong exposure to very high levels of low-density lipoprotein cholesterol (LDL-C). Untreated, patients can experience a cardiovascular event in the first decade of life. Early detection and monitoring of subclinical atherosclerosis in these patients is therefore extremely important. We set out to assess the diagnostic yield of low-dose coronary computed tomography angiography (cCTA) compared to echocardiography in detecting subclinical atherosclerosis. Methods: For this single-center cross-sectional study, we included all pediatric hoFH patients treated with lipoprotein-apheresis (LA) in Amsterdam UMC. We performed both cCTA and echocardiography in all patients as part of routine follow-up. Results: Six hoFH patients were included. Median ages at diagnosis, onset of LA and cardiovascular assessment (cCTA and echocardiography) were 2.6, 6.5, 10.8 and 11.1 years, respectively. Echocardiography revealed no signs of atherosclerosis in any of the six patients. In two patients, mild dilatation of the cardiac chambers was detected and two patients showed signs of mitral or aortic insufficiency. On cCTA, however, non-calcified plaques without stenosis were detected in four patients. In two patients calcified coronary plaques were found at the ostia of the right coronary artery or the left main coronary artery. Aortic root calcifications were found in two patients. Conclusions: Our findings suggest that in hoFH children, low-dose cCTA is superior to echocardiography for the detection of subclinical coronary and aortic root atherosclerosis and should therefore be considered in the routine cardiovascular monitoring of these high-risk children. Graphical abstract: Image 1 Highlights: Low-dose computed tomography angiography (cCTA) enables early detection of subclinical atherosclerosis in homozygous familial hypercholesterolemia (hoFH). Low-dose cCTA seems superior to echocardiography in assessing atherosclerosis. Adjusting therapy on atherosclerosis detection might impact outcome in hoFH children. Low-dose cCTA should be routinely performed in hoFH children.